Exploring Refugee Crises: A Comparative Study of US Withdrawals from Vietnam and Afghanistan (Journal of Political Science and International Relationship, 2024)
The refugee crisis is a recurring consequence of the long-term conflict and political turmoil. This research aimed to study and compare the refugee crisis resulting from the U.S. involvement in the complex political dynamics of both Vietnam and Afghanistan. The study analyzes the causes, reactions and impacts of these refugee crises and gives insights into the complexity of the displacement and international response. The qualitative research design focused on content analysis. Books, academic papers and reports are used as data sources. The framework of realist and forced migration theory was applied to identify the root causes of the refugee crisis in Vietnam and Afghanistan, allowing comparative analysis. The study examined the US military’s involvement in the refugee crisis since 1975 in Vietnam, highlighting its impact on refugees and host communities. The US’s withdrawal from Afghanistan in 2021 led to the Taliban’s takeover, increasing Afghan refugee numbers and posing political tensions and security risks. In Vietnam, an estimated 2 million and in Afghanistan, an estimated 1 million refugees fled the country after the withdrawal due to push and pull factors. The Vietnam and Afghanistan refugee crises share similarities, but they have significant differences. Vietnamese refugees primarily fled by sea, while Afghans used land, air, and sea routes. Vietnamese refugees settled in Southeast Asia and the US, while Afghan refugees sought asylum in various countries. The U.S. government’s policy response to refugees exhibited a mix of welcome and skepticism, influenced by Vietnam’s strategic importance during the Cold War. The study recommended enhancing international cooperation, prioritizing humanitarian aid, implementing comprehensive refugee policies, promoting conflict prevention, enhancing resettlement programs, addressing socioeconomic factors, raising awareness, combating stigma, strengthening legal frameworks, investing in education, and learning from past experiences to address refugee crises.